Usability Study of Digital Libraries: An Analysis of User Perception, Satisfaction, Challenges, and Opportunities at University Libraries of Nanjing, China. Issue 3 (2nd April 2017) - Jabeen, Misbah; Qinjian, Yuan; Yihan, Zhang; Jabeen, Munazza; Imran, Muhammad
ABSTRACT: Purpose : The purpose of the study was to assess the usefulness of digital library (DL) resources and the value of multidisciplinary databases among students. The study discussed perception and usage of digital databases, level of satisfaction, impact on users, factors affecting accessing digital databases, and problems in usage of digital databases. Design/methodology/approach : The survey research method was used to collect data for this study. A multi-method approach was used. The data was analyzed via SPSS (13.0). Findings : The findings reveal that most of the respondents (total mean value = 4.33, 4.26, 3.86) used DL resources for research purposes in order to fulfil their thesis/dissertation and course work requirement. A total mean value of 4.156 indicates that the respondents were extremely satisfied with the authenticity of information in available databases. Inclusion and exclusion criteria : This study included only the top five universities of Nanjing, China, according to a Chinese university rank list and the rest of the universities in China excluded from this study. The focus was on onsite users; remote users and non-users were excluded from this study. Research limitations : The study included only five universities of Nanjing, China. Therefore, a smaller size of post-graduate students was considered and a random proportionate stratified sample technique was used to make the representative sample. Practical implications : The present study will be helpful for library professionals, subject specialists, and policy makers in designing, developing, and managing university DL resources. Originality/value : This study will present valuable suggestions and contribute to the evaluation of DL resources in academic libraries from a fresh perspective.